What Works in Conservation 2019 - Sutherland, William J. (What Works in Conservation, 2019)
What Works in Conservation has been created to provide practitioners with answers to these and many other questions about practical conservation. This book provides an assessment of the effectiveness of 1389 conservation interventions based on summarized scientific evidence. The 2019 edition contains new material on bat conservation. Other chapters cover practical global conservation of primates, peatlands, shrublands and heathlands, management of captive animals as well as an extended chapter on control of freshwater invasive species, the global conservation of amphibians, bats, birds and forests, conservation of European farmland biodiversity and some aspects of enhancing natural pest control, enhancing soil fertility and control of freshwater invasive species. It contains key results from the summarized evidence for each conservation intervention and an assessment of the effectiveness of each by international expert panels. The accompanying website www.conservationevidence.com describes each of the studies individually, and provides full references. This is the fourth edition of What Works in Conservation, which is revised on an annual basis.